Field reports form, contributed by Mark A. Dietzenbach - Dietzenbach, Mark A.et al (1986)
Dietzenbach lists birds spotted in northeast Iowa during fall 1986. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of fall 1986. Epson - sheet feed/flatbed